2001
DOI: 10.1074/jbc.m011729200
|View full text |Cite
|
Sign up to set email alerts
|

DNA Synthesis and Mitotic Clonal Expansion Is Not a Required Step for 3T3-L1 Preadipocyte Differentiation into Adipocytes

Abstract: Upon differentiation induction of 3T3-L1 preadipocytes by a hormone mixture containing 1-isobutyl-3-methylxanthine, dexamethasone, and insulin, the preadipocytes undergo ϳ2 rounds of mitotic clonal expansion, which just precedes the adipogenic gene expression program and has been thought to be an essential early step for differentiation initiation. By inducing 3T3-L1 preadipocytes with each individual hormone, it was determined that the mitotic clonal expansion was induced only by insulin and not by 1-isobutyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 22 publications
(26 reference statements)
6
108
1
2
Order By: Relevance
“…38,39 The present study suggests that in mature adipocytes this signalling pathway, together with others, plays a role in the adaptation of fat cell metabolism to change in cell size. It is well established that activation of ERKs results in both transcriptional and posttransductional effects.…”
Section: Discussionmentioning
confidence: 98%
“…38,39 The present study suggests that in mature adipocytes this signalling pathway, together with others, plays a role in the adaptation of fat cell metabolism to change in cell size. It is well established that activation of ERKs results in both transcriptional and posttransductional effects.…”
Section: Discussionmentioning
confidence: 98%
“…36,[39][40][41] Most of the cell cycle related genes in our microarray were downregulated, which suggests that GSPE-treated cells were not Antiadipogenic effects of procyanidins M Pinent et al in the mitotic clonal expansion phase. Opinions on whether mitotic clonal expansion is necessary to allow adipose differentiation are controversial, 42 but recent studies support the idea that mitotic clonal expansion is required for adipogenesis. 43 In fact, Tang et al 44 demonstrated that treatment with PD98059, an inhibitor of MEK (MAPK/ extracellular signal-regulated kinase kinase), delayed mitotic clonal expansion and that this delay was proportional to decreases in differentiation markers and triacylglyceride accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report, Qiu et al (6) concluded that DNA synthesis and MCE are not required for differentiation of 3T3-L1 preadipocytes into adipocytes. In view of considerable circumstantial evidence to the contrary (29,33), were subjected to SDS͞PAGE and immunoblotting as described in Fig.…”
Section: Effect Of Mapk͞extracellular Signal-regulated Kinase Kinase mentioning
confidence: 99%
“…Treatment of growth-arrested 3T3-L1 preadipocytes with differentiation inducers initiates mitotic clonal expansion (MCE) before expression of genes that give rise to the adipocyte phenotype (3)(4)(5). Whether MCE is a prerequisite for terminal differentiation remains controversial (6), because definitive proof is lacking. This issue is addressed in the present investigation.…”
mentioning
confidence: 99%